Bubbles and information: An experiment - Matthias Sutter; Jürgen Huber; Michael Kirchler (University of Innsbruck, Department of Public Finance, 2008)
We study whether information about imminent future dividends can abate bubbles in experimental asset markets. Using the seminal design of Smith et al. (1988) we find that markets where traders are asymmetrically informed about future dividends have smaller, and shorter, bubbles than markets with symmetrically informed or uninformed traders. Hence, fundamental values are better reflected in market prices - implying higher market efficiency - when some traders know more than others about the future prospects of an asset. We also find that asymmetric information has a similar abating impact on bubbles as when uninformed traders accumulate experience, though for different reasons.
Keywords: 330; Bubbles; Asymmetrische Information; Wertpapieranalyse; Portfolio-Management; Test